2015
DOI: 10.1007/s11999-015-4400-0
|View full text |Cite
|
Sign up to set email alerts
|

Patients Undergoing Total Shoulder Arthroplasty on the Dominant Extremity Attain Greater Postoperative ROM

Abstract: Background Total shoulder arthroplasty (TSA) provides excellent functional outcomes and pain relief in appropriately selected patients. Although it is known to affect other shoulder conditions, the role of hand dominance after TSA has not been reported, to our knowledge. Questions/Purposes We asked: (1) Does TSA of the dominant arm result in greater postoperative ROM compared with TSA of the nondominant arm? (2) Does hand dominance affect validated outcome scores after TSA? Methods We performed a review of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The clinical outcomes improved significantly from preoperatively to 3 years postoperatively, with sufficiently large and consistent differences that were also clinically important because they were higher than the minimal clinically important difference determined for patients who are Measured as the highest vertebral body that the patient's thumb could reach without pain: lateral thigh = 0, buttock = 1, sacrum = 2, lumbar = 3, T12 = 4, and T7 = 5. treated for rotator cuff disease. The minimal clinically important difference, defined as the smallest change in an outcome that signifies an important improvement in a symptom, is 10°for active elevation, 9 10.4 points for the CS, 26 and 2 points for the SST 46 in patients treated for rotator cuff disease. Most clinical outcomes did not change significantly from 2 to 3 years; however, the mean improvement in active abduction was statistically significant, and this difference was the largest and most consistent among the clinical outcomes measured during this period of time.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical outcomes improved significantly from preoperatively to 3 years postoperatively, with sufficiently large and consistent differences that were also clinically important because they were higher than the minimal clinically important difference determined for patients who are Measured as the highest vertebral body that the patient's thumb could reach without pain: lateral thigh = 0, buttock = 1, sacrum = 2, lumbar = 3, T12 = 4, and T7 = 5. treated for rotator cuff disease. The minimal clinically important difference, defined as the smallest change in an outcome that signifies an important improvement in a symptom, is 10°for active elevation, 9 10.4 points for the CS, 26 and 2 points for the SST 46 in patients treated for rotator cuff disease. Most clinical outcomes did not change significantly from 2 to 3 years; however, the mean improvement in active abduction was statistically significant, and this difference was the largest and most consistent among the clinical outcomes measured during this period of time.…”
Section: Discussionmentioning
confidence: 99%
“…While there is not a set minimal clinical significant difference for shoulder ROM, previous studies suggested 10° to be clinically significant. 19 Our preoperative difference of 20° in FE and ABD between DO and ND groups appears to significantly impact patients as evidenced by their subjective rating. A recently published article described a minimal clinical significant difference of 9 points and a substantial clinical benefit of 23 points on the ASES score.…”
Section: Discussionmentioning
confidence: 76%
“…LeBlanc et al 17 found poorer outcomes in the dominant extremity when a hemiarthroplasty was performed for proximal humerus fractures. Conversely, Cvetanovich et al 19 found that dominant shoulders attain increased FE compared to their nondominant cohort when an anatomic TSA was performed. In our study, which focused on rTSA, we found the contrary-that patients who had rTSA performed on their ND extremity had a higher increase in FE and ABD than their DO cohorts.…”
Section: Discussionmentioning
confidence: 95%
“… 15 Treatment of the dominant arm has also been suggested to yield better functional outcomes after RSA, although clinical outcome scores were not affected by arm dominance. 16 …”
Section: Discussionmentioning
confidence: 99%